Tailoring alternating heteroepitaxial nanostructures in Na-ion layered oxide cathodes via an in-situ composition modulation route. (February 2018) - Huang, Qun; Liu, Jiatu; Zhang, Li; Xu, Sheng; Chen, Libao; Wang, Peng; Ivey, Douglas G.; Wei, Weifeng
Abstract: The major hurdle of room temperature sodium-ion batteries (NIBs) for large-scale energy storage applications lies in developing new electrode materials with higher energy/power densities and improved durability. This work presents a novel Na-P3/Li2 MnO3 layered composite cathode with an alternating heteroepitaxial nanostructure fabricated by an in-situ composition modulation route. XRD structural refinement, synchrotron XAS and aberration-corrected HAADF-/ABF-STEM were employed to understand the structure evolution accompanying Li substitution. It is revealed that the in-situ formation of Li2 MnO3 (Li-O'3) changes the crystallographic and chemical features of the neighboring Na-P3 layered matrix significantly and leads to the alternating Na-P3/Li-O'3 heteroepitaxial nanostructure. This alternating heteroepitaxial nanostructure delivers an extremely high reversible capacity of 210 mAh g −1 between 1.5 and 4.5 V vs. Na/Na +, much improved cycling stability and excellent electrode kinetics. Its enhanced electrochemical performance can be ascribed to the effective suppression of the P3-P3'' phase transition and subsequent amorphization upon cycling to 4.5 V. Graphical abstract: Low-temperature Li-substitution induced Na-P3/Li-O'3 heteroepitaxial nanostructure strategy is developed to improve the electrochemical performance of P3-type sodium layered oxide cathodes. Highlights: A low temperature, in-situ composition modulation strategy leads to the formation of a novel Na-P3/Li-O'3 alternating heteroepitaxial nanostructure. Enhanced capacity retention is observed in the biphasic heteroepitaxial nanostructure. The structural origin of the enhanced electrochemical performance is revealed via complementary X-ray-based spectroscopy and atomic resolution STEM. The biphasic heteroepitaxial nanostructure can effectively suppress of the P3-P3'' phase transition and subsequent amorphization upon cycling.